ОЦІНКА ПРАЦЕЗДАТНОСТІ ТІЛ КОЧЕННЯ ОПОР ТРИШАРОШ-КОВИХ БУРОВИХ ДОЛІТ ЗА КІНЕМАТИЧНИМИ ПАРАМЕТРАМИ - Яким, Р. С. (Oil and Gas Power Engineering, 2007)
The main kinematic elements of movement of three-cone rock bits bearing rolling parts are fixed. The theoretical base, which gives an opportunity to appraise the efficiency of rock bit bearing rows.